Pressure-inducing pH sensing on fiber bragg grating sensor / Nazatul Shafinaz Kamal Ariff - Kamal Ariff, Nazatul Shafinaz (2014)
This project presents an interfacing device to allow Fiber Bragg Grating function as a chemical sensor. Instead of using chemical to light conversion, this project is developed using chemical to physical conversion. The problem with existing chemical sensing using optical sensor is the fabrication process are complicated where the cladding of optical fiber is exposed causing vulnerability. This will cause optical chemical sensors are fragile and difficult to be mass produced. The objective of the project is to develop a chemical sensing using Fiber Bragg Grating sensor. However, the principle operation of Fiber Bragg Grating sensor is based on the shifted wavelength of the returned Bragg signal with the changes in physical measurands only such as strain, temperature and pressure. Since Fiber Bragg Grating sensor cannot be used for chemical sensing, this project are introduced a gripper as a transducer to allow Fiber Bragg Grating sensor function as chemical sensor where it will convert chemical sensing to physical sensing. The project is divided into the following scope (i) electronic to photonics interfacing and (ii) Fiber Bragg Grating gripper. To illustrate the functionality, we consider when the pH sensor is immersed into pH solution, it will create different voltage signal. The voltage response is feed to servo driver to drive a servo motor that coupled with gripper. The gripper is used to interface electronics sensor to optical signal where the gripper will induce different level of pressure on Fiber Bragg Grating sensor with difference pH solution: pH 4, pH 7, pH 10 and pH 12. The shifted wavelength is characterized according to the pressure level that induced by gripper. The pH solution of 12 showed the maximum value voltage response. As a result, the gripper induces Fiber Bragg Grating sensor with higher pressure and cause higher shifted wavelength.